Le Collage comme outil exploratoire collectif dans la conception d’espaces publics - Sonia Curnier; Véronique Mauron Layaz (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Today, the imagery produced by public space designers is dominated by photorealistic representations. However, some design offices deliberately choose other types of images: collages. Our study is based on the analysis of two park proposals developed in Switzerland in 2018 and 1998 that decided to use collage not for aesthetic or practical reasons, but because it engages an important conceptual decision.Through an in-depth analysis of the offices’ archives, enriched by interviews with the designers, our exploration seeks to understand the genesis of the collages, their role in the development of the project, and their meanings in the project itself and beyond.As an act of doing and thinking and an investigative tool, the collage brings out the unforeseeable and summons fiction to the heart of the project, emphasizing the unfinished and the yet-to-be-determined. Further, as a tool of prefiguration, it allows us to explore the possibilities of an uncertain future.Collage is also a collective tool, created by numerous team members in the agencies, drawing on the non-hierarchical skills of different people (architects, landscape architects, project managers, trainees, draughtsmen) and erasing the notion of authorship. Going beyond the office’s practice, it engages all audiences in the making and appropriation of public space, thus affirming its democratic value.Public Space Design, Collage, Tool, Unexpected, Collaboration